Contagious Ecthyma in Goat and Sheep: A Review of Current Status and Future Perspectives - Bhagawati, Niharika; Shankarishan, Priyanka; Habibi, Munquad (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Contagious ecthyma is a viral skin disease that affects sheep, goats, and different other domestic and wild ruminants worldwide. It is acute, contagious, and economically significant. It is a non-systematic eruptive skin condition that is significant for public health. Other names for the condition include orf disease, scabby mouth, infectious pustular dermatitis, and sore mouth. Proliferative pustules on the mouth and palate are characteristic features. These lesions normally disappear in 1-2 months. Localized proliferative and persistent skin nodule lesions, which are the hallmark and pathognomonic lesion of orf disease, come in three different types: generalized, labial, and mammary or vaginal. It can show up in either benign or malignant forms. The latter kind of orf typically leads to a significant outbreak among small ruminant populations and can be chronic and frequently lethal. The disease is brought on by orf virus-like species of the genus Parapoxvirus from the Poxviridae family. The variola virus is the biggest DNA virus and the most well-known parapoxvirus that causes smallpox. Orf virus genomes typically include 64% G+C and certain derivative patterns can be detected in particular genomic areas. Despite clinical symptoms of orf disease, a laboratory-based diagnosis is required for validation and epidermal studies. Orf disease has become more significant due to its zoonotic nature. A comprehensive understanding of the disease's various aspects could benefit the scientific community and policymakers in disease control and eradication. This review aims to provide the latest information on orf disease for effective management and a significant reduction in economic losses.